Program Sedekah Pangan Segar, Sehat, dan Ramah Lingkungan untuk Multiplier Effect di Sektor Sosial-Ekonomi Masyarakat dan Lingkungan Berkelanjutan di Masa Pandemi Covid-19 - Virtuous Setyaka; Eli Ratni; Gusti Sumarsih; Mahathir Mahathir (Warta Pengabdian Andalas, 2020)
Alms Food is a food procurement program that collects donations from any philanthrope and spends them on farmers, ranchers and Micro, Small and Medium Enterprises (MSMEs). Fresh, healthy, and environmentally friendly food are food ingredients that are produced directly by the local producers without using hazardous chemicals in the production process. The multiplier effect refers to the many benefits of action for the parties involved. The sustainable socio-economic-environmental sector is a space for community relational dynamics to produce and live together that considers present and future aspects. Furthermore, this is one of the strategies to create markets for local products so that they have targetted consumers so that production can continue, especially during the Covid-19 pandemic. This community engagement comprises three stages: preparation, implementation, and evaluation of the results. This activity had been held for 11 weeks in the target recipient locations in several sub-districts, Padang City, West Sumatra Province. This program's concept of the multiplier effect must attract and encourage other sectors to get involved, either directly or indirectly, including food producers, cooperatives, philanthropists, academics, and beneficiary community groups. It hopes that program should be continued another further weeks.